Prevalência de hipertensão arterial e seus fatores de risco entre pessoas com HIV/AIDS em uso de terapia antirretroviral - Lima, Maria Amanda Correia (2017)
This study had as objective to verify the prevalence of systemic arterial hypertension (SAH) and its risk factors among people living with HIV/aids (PLWHA) during outpatient follow-up, and to investigate the association between time of diagnosis of HIV/aids and duration of antiretroviral therapy (ART) with a prevalence of SAH and its risk factores. It is a cross-sectional, descriptive study and with quantitative approach. The project was approved by the Research Ethics Committee of the Federal University of Ceara (UFC) and all participants signed the term of free and informed consent (TCLE). The study was carried out at the Infectology Outpatient Clinic of the Walter Cantidio University Hospital (HUWC) of the UFC, with a sample of 208 patients, and the sampling process was no probabilistic for convenience. The inclusion criteria were: patients from both sexes, age range of 18 years or more, confirmed diagnosis of HIV, use the ART for at least three months. As exclusion criteria, the presence of pregnancy, persons deprived of liberty, residents in collective shelters or any other condition capable of interfering with the individual's participation in the research were recorded. Data collection was carried out from January to December 2016. Data were collected through interview with 40 minutes of duration in a privative setting. It was used a form with questions regarding patients identification, sociodemographic, clinical and epidemiological data, risk factores to SAH, blood pressure measurement, weight, hight, body mass index and waist circumference. After collection, data were organized and tabulated in the Microsoft Excel 2017® program. Statistical descriptive of continuous variables involved the calculation of mean and standard deviation.Comparisons between the strata of hypertensive and normotensive patients were made using t-test for unpaired variables.In the descriptive statistics of the categorical variables it determined the absolute and relative frequencies. The association among sociodemographic and clinical factors and the occurrence of SHA was evaluated for the chi-square test. In addition, the strength of such association was evaluated by the determination of odds ratio and its respective confidence interval of 95%. Explanatory variables associated with hypertension, at a significance level of 20% (P <0.20), were selected for the logistic regression model to identify those that, independently, constituted factors associated to SAH. The Statistical Package for Social Sciences (SPSS) software, version 20.0, was used for statistical procedures. In the results, the majority of patients were male, brown, with 9-12 years of schooling, with no children, single or married, Catholic, employed, with monthly family income greater than three wages. Most of participants were heterosexual, not living with partner, and had a serodiscordant partner. The antiretroviral drug most commonly used was Lamivudine.17.3% of the sample already had a confirmed diagnosis of SAH. Regarding risk factors, it was observed that PLWHA with SAH had higher mean age (P <0.001), higher waist circumference (P <0.001), more time of infection (P = 0.005) and of use of ART (P= 0.002). It was observed that PLWHA were more likely to have SAH when they were older than 45 years (P = 0.003), had a family history of SAH (P = 0.003), overweight (P = 0.024), increased abdominal circumference (P = 0.013) and time of ART use over 36 months (P <0.001). The results of the analyzes demonstrated that the risk of SAH increases according to individuals age over 45 years (P = 0.010), family history of SAH (P = 0.005), overweight (P = 0.019) and time of use of ART greater than 36 months (P = 0.002).It is concluded that people with HIV/aids older than 45 years, family history of hypertension, overweight and in ART for more than 36 months are more likely to be hypertensive, being the prevalence of hypertension in this study 17.3%.